COVID-19 fosters social accountability in medical education - Richard Murray; Fortunato Cristobal; Shrijana Shrestha; Filedito Tandinco; Jan De Maeseneer; Sarita Verma; Shafik Dharamsi; Sara Willems; Arthur Kaufman; Björg Pálsdóttir; Andre-Jacques Neusy; Sarah Larkins (James Cook University, 2022)
The COVID-19 pandemic has highlighted embedded inequities and fragmentation in our health systems. Traditionally, structural issues with health professional education perpetuate these. COVID-19 has highlighted inequities, but may also be a disruptor, allowing positive responses and system redesign. Examples from health professional schools in high and low- and middle-income countries illustrate pro-equity interventions of current relevance. We recommend that health professional schools and planners consider educational redesign to produce a health workforce well equipped to respond to pandemics and meet future need.